1969
DOI: 10.1515/cclm.1969.7.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Comparative trial with highly purified natural ACTH, synthetic ACTH 1—24 peptide and synthetic ACTH 1—39 peptide

Abstract: Brombacher, Buytendijk and Maesen: Comparative trial with natural ACTH and synthetic ACTH peptides 291 Z. klin. Chem. u. klin. Biochem. 7. Jg., S. 291-292, Mai 1969 Comparative trial with highly purified natural ACTH, synthetic ACTH 1-24 peptide and synthetic ACTH 1-39 peptide The intensity and duration of the adrenocortical stimulation^ produced by highly purified natural porcine ACTH (44 U/m/), synthetic ACTH 1-24 peptide (0.44 mg tetracosapeptide/m/) and synthetic ACTH 1-39 peptide (0.4 mg l-39 peptide/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Since therapeutic use of ACTH analog formulations became widespread in the 1950s and 1960s, studies have demonstrated variable cortisol responses after administration of different ACTH products. 24 , 25 , 33 , 34 This phase 1, single‐center, open‐label, randomized parallel group study is the first to report a direct comparison of the cortisol responses of RCI and synthetic ACTH 1‐24 depot.…”
Section: Discussionmentioning
confidence: 99%
“…Since therapeutic use of ACTH analog formulations became widespread in the 1950s and 1960s, studies have demonstrated variable cortisol responses after administration of different ACTH products. 24 , 25 , 33 , 34 This phase 1, single‐center, open‐label, randomized parallel group study is the first to report a direct comparison of the cortisol responses of RCI and synthetic ACTH 1‐24 depot.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous ACTH potently induces cortisol production 25 ; however, the steroidogenic effects of different ACTH drug class formulations are known to be variable. 20 , 26 For example, a comparison of synthetic ACTH 1‐24 , synthetic ACTH 1‐39 , and a porcine‐derived ACTH formulation (Organon, Inc.) demonstrated a higher corticosteroid response with the porcine‐derived ACTH than with the other ACTH formulations. 26 These data are in contrast to our results showing that synthetic ACTH 1‐24 depot was more steroidogenic than repository corticotropin injection.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 26 For example, a comparison of synthetic ACTH 1‐24 , synthetic ACTH 1‐39 , and a porcine‐derived ACTH formulation (Organon, Inc.) demonstrated a higher corticosteroid response with the porcine‐derived ACTH than with the other ACTH formulations. 26 These data are in contrast to our results showing that synthetic ACTH 1‐24 depot was more steroidogenic than repository corticotropin injection. In addition, the corticosteroid response to the synthetic ACTH 1‐24 depot used in our study and the ACTH 1‐24 used by Brombacher et al were similar, suggesting that the porcine‐derived ACTH formulation studied by Brombacher induces a greater corticosteroid response than repository corticotropin injection.…”
Section: Discussionmentioning
confidence: 99%
“…12 ACTH is available as a natural product and as a synthetic analog. 13 Outside the United States, synthetic analogs of ACTH-synthetic ACTH 1-24 (tetracosactide) and synthetic ACTH 1-39 (corticotropin carboxymethyl-cellulose [CCMC])-are used. 6,14 The efficacy of RCI may differ from that of synthetic ACTH treatments based on the structure of peptide; 15 however, there are no head-to-head trials comparing the efficacy of RCI and synthetic ACTH treatments.…”
Section: Introductionmentioning
confidence: 99%